“I never get a thing that ain’t been used”: A diachronic corpus-based study of second-hand consumption - Gilquin Gaëtanelle (Journal of World Languages, 2022)
Second-hand consumption is often seen as a way of reducing one’s ecological footprint. In an attempt to find out how the representations of second-hand consumption in discourse have evolved over time, a corpus study of the word second-hand is carried out on the basis of the Corpus of Historical American English (COHA) (1820–2019). Frequency is considered, as well as collocates, which show the types of second-hand items that are mentioned in different time periods and which indicate how positively or negatively connoted second-hand consumption is. Together with a more qualitative approach, this analysis reveals variation in the frequency and connotations of the word second-hand, and some long-lasting stigma which survives for example through comparisons. The article ends with some suggestions as to how the image of second-hand consumption could be improved.